2014
DOI: 10.1007/s00227-014-2577-5
|View full text |Cite
|
Sign up to set email alerts
|

Small pelagic fish feeding patterns in relation to food resource variability: an isotopic investigation for Sardina pilchardus and Engraulis encrasicolus from the Bay of Biscay (north-east Atlantic)

Abstract: Small pelagic fish represent an essential link between lower and upper trophic levels in marine pelagic ecosystems and often support important fisheries. In the Bay of Biscay in the north-east Atlantic, no obvious controlling factors have yet been described that explain observed fluctuations in European sardine Sardina pilchardus and European anchovy Engraulis encrasicolus stocks, in contrast to other systems. The aim of this study was therefore to investigate to which extent these fluctuations could be tropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 90 publications
2
23
0
1
Order By: Relevance
“…Similarities in the helminth parasites of S. pilchardus and E. encrasicolus recorded both in our field study (three species of Ascaridoidea in the Bay of Biscay) and in their entire geographical distribution (12 trophically-transmitted taxa in common among Digenea, Cestoda, Nematoda and Acanthocephala) highlighted feeding similarities. Such similarities have been previously demonstrated between these two small planktivorous pelagics using analyses of stomach contents and stable isotopes despite a greater trophic plasticity for E. encrasicolus (Morello and Arneri 2009;Chouvelon et al 2014Chouvelon et al , 2015. In the Bay of Biscay, S. pilchardus and E. encrasicolus mainly feed with small-to medium-sized copepods (e.g., Acartia sp.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Similarities in the helminth parasites of S. pilchardus and E. encrasicolus recorded both in our field study (three species of Ascaridoidea in the Bay of Biscay) and in their entire geographical distribution (12 trophically-transmitted taxa in common among Digenea, Cestoda, Nematoda and Acanthocephala) highlighted feeding similarities. Such similarities have been previously demonstrated between these two small planktivorous pelagics using analyses of stomach contents and stable isotopes despite a greater trophic plasticity for E. encrasicolus (Morello and Arneri 2009;Chouvelon et al 2014Chouvelon et al , 2015. In the Bay of Biscay, S. pilchardus and E. encrasicolus mainly feed with small-to medium-sized copepods (e.g., Acartia sp.…”
Section: Discussionsupporting
confidence: 57%
“…and Temora sp.) (Chouvelon et al 2014(Chouvelon et al , 2015. These copepods probably act as intermediate hosts for the Ascaridoidea recorded here; S. pilchardus and E. encrasicolus serving as trophic links in both Anisakis and Hysterothylacium life cycles (Køie 1993;Mattiucci and Nascetti 2008;Kijewska et al 2009).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the Gulf of Lions, Pethybridge et al (2014) reported that no competition of sprats with anchovies and sardines during winter 2011 was apparent on the basis of lipid biomarkers. In the Bay of Biscay, Chouvelon et al (2015) hypothesised that anchovies and sardines are potential competitors for food in autumn, but not in spring.…”
Section: Interaction Between Planktivorous Teleost Speciesmentioning
confidence: 99%
“…Jenis ikan pelagis kecil di Laut Banda antara lain ikan layang, selar, belanak, julungjulung, ikan terbang, teri, tembang, lemuru, golok-golok, dan kembung. Ikan pelagis kecil merupakan elemen penting dari ekosistem laut karena berada di tingkat menengah dalam jaringjaring makanan, sehingga memainkan peran yang cukup penting dalam menghubungkan (-37,90) -(-37,70) tingkat bawah dan atas tropik makanan (Checkley et al 2009;Chouvelon et al 2015). Populasi ikan pelagis kecil berfluktuasi disebabkan oleh variabilitas lingkungan dan karena siklus hidup yang relatif singkat (2-3 tahun) (Palomera et al 2007).…”
Section: Hasil Dan Pembahasan Pendekatan Nilai Ts Terhadap Panjang Ikanunclassified